2018
DOI: 10.1101/365122
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alternative (backdoor) androgen production and masculinization in the human fetus

Abstract: 2Masculinization of the external genitalia in humans is dependent on formation of 5α-3 dihydrotestosterone (DHT) through both the canonical androgenic pathway and an alternative 4 (backdoor) pathway. The fetal testes are essential for canonical androgen production but little 5 is known about the synthesis of backdoor androgens despite their known critical role in 6 masculinization. In this study, we have measured plasma and tissue levels of endogenous 7 steroids in second trimester human male fetuses using mul… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 64 publications
1
8
0
2
Order By: Relevance
“…Here, no 7α‐OHT was found in adult testes, while 5α‐DHT was undetectable in fetal testes (Table 1). The lack of fetal testicular DHT is concurrent with a study indicating the absence of DHT in fetal plasma 27 . Metabolic activities of both 3α‐HSD and 5α‐reductase are inhibited by 7α‐OHT and 7α‐Adione in adult rat testes, 28 which might explain ααβ‐diol catalyzed by 3α‐HSD was not detected here.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Here, no 7α‐OHT was found in adult testes, while 5α‐DHT was undetectable in fetal testes (Table 1). The lack of fetal testicular DHT is concurrent with a study indicating the absence of DHT in fetal plasma 27 . Metabolic activities of both 3α‐HSD and 5α‐reductase are inhibited by 7α‐OHT and 7α‐Adione in adult rat testes, 28 which might explain ααβ‐diol catalyzed by 3α‐HSD was not detected here.…”
Section: Discussionsupporting
confidence: 87%
“…The lack of fetal testicular DHT is concurrent with a study indicating the absence of DHT in fetal plasma. 27 Metabolic activities of both 3α-HSD and 5α-reductase are inhibited by 7α-OHT and 7α-Adione in adult rat testes, 28 which might explain ααβ-diol catalyzed by 3α-HSD was not detected here. In addition, 7α-Adione in a Leydig cell was significantly higher in fetus than in adults (P < .04).…”
Section: Discussionmentioning
confidence: 69%
“…Whether this is the case, or indeed whether this explains the apparent dispensability of Hsd17b3 for basal testosterone production requires further investigation. A further explanation could be that, in humans, masculinization requires that both canonical and alternative (backdoor) androgen pathways are intact and the alternative pathway may also be dependent on a functional HSD17B3 38,39 . This alternative pathway does not appear to be of importance in fetal masculinization in the mouse 40 …”
Section: Discussionmentioning
confidence: 99%
“…The alternative (backdoor) androgen synthesis pathway has been reported in human hyperandrogenic disorders, such as prenatal virilization/masculinization in girls with congenital adrenal hyperplasia (CAH), or with prepubertal acne [5]. Studies have demonstrated that androsterone is the principal backdoor androgen in the human fetus, and its circulating level is sex‐dependent.…”
Section: Androgen Biosynthesismentioning
confidence: 99%
“…The backdoor androgens are primarily synthesized from the placental progesterone in several nontesticular tissues, with little de novo biosynthesis in the testis. This explains the relationship between placental insufficiency and sex development disorders [5]. The expression of aldo‐keto reductases (AKR1C1‐1C4), 5α‐reductases (SRD5A1/2), and retinol dehydrogenase (RoDH) in the ovarian theca cells is enhanced in the polycystic ovary syndrome (PCOS), revealing that backdoor DHT biosynthesis occurs in the ovary and plays significant roles in androgen overproduction and clinical hyperandrogenism (HA) [6].…”
Section: Androgen Biosynthesismentioning
confidence: 99%